Pengaruh pengawasan fungsional, pengelolaan keuangan, dan kejelasan sasaran anggaran terhadap akuntabilitas kinerja inspektorat kota malang - Maria Novriana Mina; Anwar Made; Rita Indah Mustikowati (Jurnal Riset Mahasiswa Akuntansi, 2020)
This research was conducted to examine and determine the effect of functional supervision, financial management, and clarity of budget targets on the performance accountability of the Inspectorate of Malang. This type of research is quantitative research, the source of the data used is primary data, sampling techniques using total sampling method, then analyzed with multiple linear regression models. The results showed that functional oversight, financial management and clarity of budget objectives simultaneously affect performance accountability, functional supervision partially influences performance accountability, financial management influences performance accountability and clarity of budget targets affects performance accountability